As indústrias têxtil e do vestuário na Comunidade Económica Europeia. Os novos factores de competitividade - Pires, Iva (Finisterra, 1995)
THE EEC TEXTILE AND CLOTHING INDUSTRIES, THE NEW COMPETITIVE ADVANTAGES - In spite of using new technologies, the textile and clothing industries remain intensive in workforce and thus sensitive to wage costs. The European firms must therefore find other competitive advantages based on product differentiation, quality and design. German and Italian T&C industries are good examples of how quality and design can help "mature" industries maintain a successful place in the world market. Nevertheless, the cost of production remains a problem. The use of the outwear processing traffic (OPT) allows the European textile industry to mantain the quality patterns of its products, profiting from cheap workforce. This more advantageous situation is due both to innovation and to low production costs.